PENGARUH AUDIT FIRM STATUS, AUDIT COMPLEXITY, KEPEMILIKAN KELUARGA, DAN LOSS TERHADAP AUDIT REPORT LAG DENGAN SPESIALISASI INDUSTRI SEBAGAI VARIABEL MODERASI - Vinola Herawaty; Muhammad Farhan Rusmawan (Lembaga Penelitian Universitas Trisakti, 2019)
The purpose of this study is to show the influence of audit firm status, auditcomplexity, family ownership, and loss with industrial specialists auditor asmoderating variable to audit report lag.The sample used in this study is based on the main sector manufactures on the Indonesia Stock Exchange (IDX) during the period 2015-2017. By using purposive sampling method obtained sample asmany as 161 companies that have been in selection and meet the criteria.Theresults of this study indicate that loss has a positive effect on audit report lag,audit firm status and audit complexity do not have positive effects on audit report lag. Then, family ownership and industry specialization do not have the negative effect on audit report lag. In addition, industry specialization do not stengthen the negative effects of audit firm status and family ownership on audit report lag. Meanwhile, industry specialization does not weaken the positive effect of audit complexity and loss on audit report lag.